Health Education Analysis Of Adolescent Behavior Regarding Free Sex In Karadiri Village Wanggar District, Nabire District - Tety Ripursari; Sari Pratiwi Apidianti; Jumaati; Matrahman; Arantrinita; Arifin; Zainal Andy Saputra (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
The lack of provision of health education to adolescents about sex as well as the rapid development of internet media such as free access to pornographic content has caused adolescents' sexual behavior to become more risky and to influence behavior that is not good about sex. The purpose of this study was to analyze the effect of health education on adolescent behavior regarding free sex in Karadiri Village, Wanggar District, Nabire Regency. The research design used pre-experimental research with a one group pre test-post test design. The sample for this study were 42 adolescents aged 15-21 years in Karadiri Village in June 2023. Sampling method using Simple Random sampling technique. Data collection using a questionnaire. Bivariate analysis used the Wilcoxon statistical test with a significant level of α = 0.05. Based on the results of the study that out of 42 respondents, most of the respondents before being given health education had negative sexual behavior as many as 22 respondents (52.3%) and after being given health education almost all respondents had positive sexual behavior as many as 40 respondents (95.2%). The Wilcoxon test results obtained p = 0.000 <0.05, so H1 is accepted or Ho is rejected, meaning that there is an effect of sexual health education on adolescent behavior regarding free sex in Karadiri Village, Wanggar District, Nabire Regency. Providing sexual health education has an important role in providing knowledge to teenagers to have positive behavior and prevent promiscuous sexual behavior.